2014
DOI: 10.1371/journal.pone.0087031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hyperpolarized [1-13C]-Pyruvate by Magnetic Resonance to Detect Ionizing Radiation Effects in Real Time

Abstract: Ionizing radiation (IR) cytotoxicity is primarily mediated through reactive oxygen species (ROS). Since tumor cells neutralize ROS by utilizing reducing equivalents, we hypothesized that measurements of reducing potential using real-time hyperpolarized (HP) magnetic resonance spectroscopy (MRS) and spectroscopic imaging (MRSI) can serve as a surrogate marker of IR induced ROS. This hypothesis was tested in a pre-clinical model of anaplastic thyroid carcinoma (ATC), an aggressive head and neck malignancy. Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 43 publications
4
71
0
Order By: Relevance
“…Tumor metabolism was challenged using 2DG (31) (N=9), external radiation therapy (32) (N=7), or conditional gene expression (19) (N=3); controls were tested prior to or without perturbation (N=33) or administered a negative control (N=3). All three kinetic models fit these datasets (N=55) reasonably well, as summarized in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor metabolism was challenged using 2DG (31) (N=9), external radiation therapy (32) (N=7), or conditional gene expression (19) (N=3); controls were tested prior to or without perturbation (N=33) or administered a negative control (N=3). All three kinetic models fit these datasets (N=55) reasonably well, as summarized in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…For orthotopic tumors, U-HTH83 luciferase expressing cells (2.5×10 5 /mouse) were injected into the right thyroid lobe under direct visualization as previously described. (5) For flank tumors, cells (2×10 6 /mouse) were injected into both flanks of each animal. Tumor size was ascertained regularly throughout the experimental period using bioluminescence imaging and manual measurements as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…(510) IR-induced ROS perturb cellular metabolism in a measurable and quantifiable manner which could theoretically be exploited for therapeutic purposes. (5) Our group has demonstrated a proportional relationship between IR-induced ROS levels and cell death, and showed that this relationship at least partially accounts for some of the radioresistance encountered in solid tumors. (6, 8) This relationship identifies an important therapeutic window to target radioresistant tumors, such as those driven by mutations in TP53.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Many studies have demonstrated detection of aerobic glycolysis using hyperpolarized 13 C-labeled pyruvate to be a robust probe of cancer metabolism, correlating with disease presence, stage, and response to therapy. 2,[11][12][13][14] Researchers have successfully completed testing the use of HP-pyruvate in phase 1 clinical trials 13 in prostate cancer patients, with trials in patients with cancer at other sites scheduled to start soon.…”
Section: Introductionmentioning
confidence: 99%